Effect of Spare-Part Replacement and Machine Modification on Yarn Breakage Reduction in Type L Twist For One (TFO) Machine - Filly Pravitasari Filly; Feny Nurherawati; Lupi Sugianto; Luciana (Politeknik META Industri Cikarang, 2026)
Background High yarn breakage during the twisting process in Twist For One (TFO) machines significantly reduces production efficiency and increases the proportion of Grade B yarn. Although machine maintenance is routinely performed, limited studies have experimentally evaluated the effectiveness of specific spare-part replacement and machine modification in minimizing yarn breakage and improving yarn quality Purpose This study aims to identify the dominant causes of yarn breakage and evaluate the effectiveness of bearing bolster replacement and pipe tensor modification in reducing yarn breakage and improving yarn quality on the Murata 310 Type L CPU TFO machine. Methodology An experimental approach employing a One Group Pretest–Posttest design was used by comparing machine performance before and after corrective actions. Data were collected through direct observation, interviews, documentation, and spare-part inspections. A Fishbone (Ishikawa) analysis was conducted to identify the root causes of yarn breakage, followed by the implementation of bearing bolster replacement and pipe tensor modification on 17 Murata 310 Type L CPU TFO machines. Findings The Fishbone analysis identified the machine factor as the primary cause of yarn breakage, particularly worn bearing bolsters, improper rotary disk clearance, and an unsuitable pipe tensor configuration that caused unstable yarn ballooning. After implementing the proposed improvements, the percentage of Grade B yarn decreased from 14.7% to 8.9%, representing a 5.8% reduction, while the proportion of Grade A yarn increased accordingly. These results demonstrate that bearing bolster replacement and pipe tensor modification effectively improve yarn winding stability, reduce yarn breakage, and enhance overall product quality. Implications The proposed maintenance strategy provides a practical approach for improving production efficiency and yarn quality in textile manufacturing. Future studies should evaluate the long-term effectiveness of condition-based preventive maintenance, investigate its economic impact, and validate the proposed modifications across different TFO machine models and operating conditions. Originality This study contributes by experimentally validating the combined effect of bearing bolster replacement and pipe tensor modification on the performance of the Murata 310 Type L CPU TFO machine. Unlike previous studies that primarily focused on identifying the causes of yarn breakage, this research demonstrates a practical maintenance intervention capable of significantly reducing yarn breakage and improving yarn quality in an industrial production environment.